Argentinean Real Exchange Rate 1900-2006: Testing Purchasing Power Parity Theory - del Bianco, Marco (Estudios de Economía, 2016)
This paper tests the Purchasing Power Parity Theory of Exchange Rates dealing with Argentinean data for the period 1900-2006. This is equivalent to testing if the Real Exchange Rate is a stationary variable or if its components (the nominal exchange rate and the relative prices) are cointegrated. Since most works study developed countries or developing countries but with short span data, this paper aims to fill a gap in the wide PPP literature by studding a developing country with a long-run approach. This country is particularly interesting since during 20th century “Argentine economic performance tells a story of decline unparalleled in modern times” (Taylor 1992). The downfall of this once developed country has probably affected the behavior of its RER and the validity of PPP. To check this, we use a wide set of econometric techniques and found that the PPP theory is not verified in Argentina, since its RER appears as a non-stationary variable, and there is no evidence of cointegration between the nominal exchange rate and the relative prices. In particular, the Argentinean RER appears to be trend-stationary under structural breaks with a continuous real depreciation of the Argentinean currency, especially in the first half of XX century, which is consistent with theories that relate the secular impoverishment of a country with the depreciation of its RER, as the Balassa-Samuelson effect.